Supporting Iraqi Kurdistan Health Authorities in Post-conflict Recovery: The Development of a Health Monitoring System - Emberti Gialloreti, Leonardo; Basa, Faiq B.; Moramarco, Stefania; Salih, Adil O.; Alsilefanee, Haveen H.; Qadir, Sivar A.; Bezenchek, Antonia; Incardona, Francesca; Di Giovanni, Daniele; Khorany, Revan; Alhanabadi, Luma H. H.; Salih, Shahla O.; et al. (Frontiers in Public Health, 2020)
Background: In recent decades, Iraq has endured several conflicts and socio-political tensions, that have disrupted the public health system. Nowadays, because health data are not yet collected on a routine basis, the country still lacks proper health statistics and, consequently, response plans to meet the health needs of its population. Therefore, one of the main priorities of Iraqi post-conflict agenda appears to be the reconstruction of a full-fledged health system. Methods: In 2015, the University of Rome Tor Vergata and the Ministry of Health of the Iraqi Kurdistan Region established a project to develop a Health Monitoring System for epidemiological surveillance. Its objective is to assist health authorities in collecting, analysing, and interpreting health data (coded using the International Statistical Classification of Diseases ICD-10) to support evidence-based health policy decisions, as well as to develop a public health culture among health personnel by strengthening their management capacity. Results: By September 2019, the primary health centres and hospitals included in the Health Monitoring System were 59: 25 in Duhok governorate, 16 in Erbil, 15 in Sulaimaniya, and 3 in Halabja. At present, approximately 600,000 disease events have been collected. Seminars and practical training sessions were organized to increase the integration, processing and analysis of data among the personnel of the public health system. The participants were introduced also to the basic concepts of data-driven decision making. Overall, 734 medical doctors, nurses, statisticians, and public health officials have been trained on these topics. The goal during the next three years is to reach 120 operative centers within the region (at least 50% of the overall main health facilities in KRG), envisaging a subsequent expansion of the system to all Iraq. Conclusions: The provision of an epidemiological surveillance system will allow routine collection of comprehensive information about the health of the population, thus facilitating prompt responses to present and emerging needs and improving access to and the quality of public healthcare. The health information system will guide the formulation and evaluation of health policies, providing useful data for evidence-based decision-making, long-term planning, and policy development, possibly triggering appropriate and cost-effective interventions.